2019
DOI: 10.1007/s00429-019-01988-5
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the straight-ahead preference in human visual cortex

Abstract: The objects located straight-ahead of the body are preferentially processed by the visual system. They are more rapidly detected and evoke stronger BOLD responses in early visual areas than elements that are retinotopically identical but located at eccentric spatial positions. To characterize the dynamics of the underlying neural mechanisms, we recorded in 29 subjects the EEG responses to peripheral targets differing solely by their locations with respect to the body. Straight-ahead stimuli led to stronger res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Whatever the feedforward or feedback nature of the propagation of the straight-ahead preference, this phenomenon can be considered as a mechanism of spatial attention: it serves allocating more neuronal resources for the visual analysis of a behaviourally relevant portion of the surrounding space. In line with this idea, the neural gain increases measured for straight-ahead stimuli in primary visual cortex (Strappini et al 2015) and at early latencies (Bogdanova et al 2020) are similar to those observed when manipulating attention (see, e.g., Kastner et al 1999or Liu et al 2005 for fMRI studies and Hillyard and Anllo-Vento 1998 for EEG findings). Classically, spatial attention mechanisms fall into one of 2 classes.…”
Section: Locations and Nature Of The Involved Modulatory Signalssupporting
confidence: 66%
See 4 more Smart Citations
“…Whatever the feedforward or feedback nature of the propagation of the straight-ahead preference, this phenomenon can be considered as a mechanism of spatial attention: it serves allocating more neuronal resources for the visual analysis of a behaviourally relevant portion of the surrounding space. In line with this idea, the neural gain increases measured for straight-ahead stimuli in primary visual cortex (Strappini et al 2015) and at early latencies (Bogdanova et al 2020) are similar to those observed when manipulating attention (see, e.g., Kastner et al 1999or Liu et al 2005 for fMRI studies and Hillyard and Anllo-Vento 1998 for EEG findings). Classically, spatial attention mechanisms fall into one of 2 classes.…”
Section: Locations and Nature Of The Involved Modulatory Signalssupporting
confidence: 66%
“…Altogether, these two studies demonstrated that straight-ahead effects are also observable in the human occipital cortex (notably in area V1, Strappini et al 2015 ) as early as 65–70 ms after stimulus onset (Bogdanova et al 2020 ). If these results are generally compatible with those observed in monkey electrophysiology, (Durand et al 2010 , see Sect. "…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations